The Mediating Role of Knowledge Sharing Behavior on the Effect of Person-Organization Fit on Innovative Work Behavior - Lidya Natalia; Christine Winstinindah Sandroto (AIBPM Publisher, 2020)
This study aims to determine the effect of person-organization on fit on innovative work behavior mediated by knowledge sharing behavior. The population in this study were all employees of Ebiz Corporation. The sample size, determined through Slovin formula, and 74 samples were obtained. The sampling technique is convenience sampling. The data analysis method used in this study is path analysis using analytical tools from Preacher – Hayes, The Simple Mediator Model. From the research findings, the knowledge sharing behavior is proven to mediate the effect of person-organization fit on innovative work behavior.